2006
DOI: 10.1038/sj.bjc.6602971
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of retinoic acid metabolism blocking agents (RAMBAs) on the growth of human prostate cancer cells and LNCaP prostate tumour xenografts in SCID mice

Abstract: In recent studies, we have identified several highly potent all-trans-retinoic acid (ATRA) metabolism blocking agents (RAMBAs). On the basis of previous effects of liarozole (a first-generation RAMBA) on the catabolism of ATRA and on growth of rat Dunning R3227G prostate tumours, we assessed the effects of our novel RAMBAs on human prostate tumour (PCA) cell lines. We examined three different PCA cell lines to determine their capacity to induce P450-mediated oxidation of ATRA. Among the three different cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…This result supports the hypothesis that RAMBA VN/14-1 is able to enhance the biological activity of ATRA through the inhibition of ATRA in vivo. We have demonstrated previously this effect in in vitro breast and prostate cancer models (Patel et al, 2004;Huynh et al, 2006).…”
Section: In Vivo Antitumour Study Of Atra 4-hpr and Rambasmentioning
confidence: 54%
See 3 more Smart Citations
“…This result supports the hypothesis that RAMBA VN/14-1 is able to enhance the biological activity of ATRA through the inhibition of ATRA in vivo. We have demonstrated previously this effect in in vitro breast and prostate cancer models (Patel et al, 2004;Huynh et al, 2006).…”
Section: In Vivo Antitumour Study Of Atra 4-hpr and Rambasmentioning
confidence: 54%
“…Our RAMBAs are also considered to be atypical, because in addition to being potent inhibitors of ATRA metabolism (able to enhance the antiproliferative action of ATRA), they also possess intrinsic potent cancer antiproliferative activities (Njar et al, 2000(Njar et al, , 2006aNjar, 2002;Patel et al, 2004;Huynh et al, 2006;Belosay et al, 2006). We have also found that our RAMBAs appear to have different potencies in different types of human cancer cell lines.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Our RAMBAs, however, based on the retinoid scaffold are considered 'atypical RAMBAs', because they are also endowed with multiple anticancer activities. On the basis of several studies in our lab, it is now evident that the anticancer activities of our RAMBAs cannot be explained by inhibition of ATRA metabolism alone (Patel et al, 2004(Patel et al, , 2007bGediya et al, 2005;Belosay et al, 2006;Huynh et al, 2006). We recently examined the growth inhibitory effects of one of our lead atypical RAMBAs VN/ 66-1 ( Figure 1A) in combination with clinically used suberoylanilide hydroxamic acid (SAHA, a HDACI) on the androgen receptor-positive human prostate LNCaP cell line (Gediya et al, 2005).…”
mentioning
confidence: 99%